2021
DOI: 10.1186/s40795-021-00444-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimum acceptable diet practice and its associated factors among children aged 6–23 months in rural communities of Goncha district, north West Ethiopia

Abstract: Background After the first 6 months breast milk is no longer sufficient to meet the nutritional needs of the infant. Therefore, complementary foods should be added to the child’s diet. Feeding children with a diversified diet is practiced improperly in developing countries including Ethiopia particularly in the rural community of the Amhara region. However, limited information was documented on the rural communities and no data were available specifically in the study area to show the exact pic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 15 publications
(17 reference statements)
10
27
0
Order By: Relevance
“…Children from lower-middle and higher middle-income level countries also have less chance to have inadequate MDD as compared to lower-income levels. This is in line with a study conducted in India (27,61,62), Bangladesh (47), South Asia (22), Tanzania (25), and Ethiopia (12,55,56), but other studies in Ethiopia showed that no association with it (10,14). This difference might be due to the small sample size and covers the small district of the latter two studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Children from lower-middle and higher middle-income level countries also have less chance to have inadequate MDD as compared to lower-income levels. This is in line with a study conducted in India (27,61,62), Bangladesh (47), South Asia (22), Tanzania (25), and Ethiopia (12,55,56), but other studies in Ethiopia showed that no association with it (10,14). This difference might be due to the small sample size and covers the small district of the latter two studies.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that, as the educational status of women improves, so do their chances of having children who did not access MDD. This is supported by a study conducted in Indonesia (9), Bangladesh (47), South Asia (22), India (27), Tanzania (25), Ghana (53), and Ethiopia (14,(54)(55)(56). Mothers' knowledge of child feeding was positively associated with MDD in childfeeding practice (10,12,54).…”
Section: Discussionmentioning
confidence: 63%
“…The current study also pointed out that infants and children of households with medium and highest wealth indexes were more likely to receive the minimum acceptable diet compared to those with the lowest wealth index. This finding was similar to studies conducted in South Kivu, Democratic Republic of Congo [ 46 ], Philippines [ 49 ], and Goncha district, north West Ethiopia [ 48 ]. This may be due to the fact that diversifying diet and frequent feeding relies on the income of the households to secure their diet, which may be a difficulty for low-income countries like Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…The odds of receiving the minimum acceptable diet were higher among mothers who attended primary school and above educational levels compared to those who had no formal education. This finding was supported by previous studies from South Kivu, Democratic Republic of Congo [ 46 ], Dembecha district, Northwest Ethiopia [ 47 ], and Goncha district, Northwest Ethiopia [ 48 ]. This may be due to the fact that those who attended education might have the chance to learn about diet and child feeding practices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation